Maladaptive changes in the homeostasis of AEA-TRPV1/CB1R induces pain-related hyperactivity of nociceptors after spinal cord injury - JiaQi Hu; WenYong Fan; Yue Xu; XiaoFei Li; HaoYang Zhang; Shun Li; Lei Xue (Cell & Bioscience)
Abstract Background Neuropathic pain resulting from spinal cord injury (SCI) is associated with persistent hyperactivity of primary nociceptors. Anandamide (AEA) has been reported to modulate neuronal excitability and synaptic transmission through activation of cannabinoid type-1 receptors (CB1Rs) and transient receptor potential vanilloid 1 (TRPV1). However, the role of AEA and these receptors in the hyperactivity of nociceptors after SCI remains unclear. Results In this study, we investigated the effects of AEA and its receptors on the hyperexcitability of mouse dorsal root ganglion (DRG) neurons after SCI. Using a whole-cell patch-clamp technique, we found that the timing of SCI-induced hyperexcitability in nociceptors paralleled an increase in the endocannabinoid AEA content. The expression of TRPV1 and CB1R was also upregulated at different time points after SCI. High-dose extracellular administration of AEA increased the excitability of naive DRG neurons, leading to the transition from a rapidly accommodating (RA) hypoexcitable state to a highly excitable non-accommodating (NA) state. These AEA-induced transitions were facilitated by increased TRPV1 transcription. Pharmacological and Ca2+ imaging experiments revealed that AEA induced hyperexcitability in nociceptors after SCI via the AEA-TRPV1-Ca2+ pathway, whereas activation of CB1Rs reduced SCI-induced hyperexcitability and maintained cytosolic Ca2+ concentration ([Ca2+]cyto) at low levels in the early stages of SCI. As the AEA and TRPV1 levels increased after SCI, adaptive neuroprotection transitioned to a maladaptive hyperactive state, leading to sustained pain. Conclusions Taken together, this study provides new insights into how endocannabinoids regulate nociceptor activity after SCI, offering potential targets for the treatment of neuropathic pain.